Acute subdural hematoma after aortic surgery: A retrospective comparative study. (January 2015) - Osada, Hiroaki; Marui, Akira; Tanaka, Shiro; Meshii, Katsuaki; Ohnaka, Motoaki; Nakajima, Hiroyuki
Background: Acute subdural hematoma is uncommon following open-heart surgery, but may result in increased mortality and morbidity. Methods: A retrospective analysis was performed involving all patients who underwent thoracic aortic surgery from January 2009 to February 2013. There were 53 patients who had thoracic aortic repair with open distal anastomosis and required selective cerebral perfusion with or without retrograde cerebral perfusion. We evaluated the incidence of postoperative acute subdural hematoma. The patients were divided into two groups: a subdural hematoma group who had symptomatic subdural hematoma postoperatively, and a non-subdural hematoma group who had no subdural hematoma. The variables were compared between the 2 groups. Results: Eight (15.1%) patients had a transient symptomatic subdural hematoma; none required surgical evacuation of the hematoma. There were significant differences between the two groups in terms mean and maximum retrograde cerebral perfusion flow, and the volume of intraoperative platelet transfusion. Multivariate analysis revealed that a significant risk factor for acute subdural hematoma following thoracic aortic surgery was the amount of intraoperative platelet transfusion (odds ratio = 0.9, 95% confidence interval: 0.81–0.98, p = 0.015). Conclusions: This retrospective study demonstrated that the subdural hematoma group received fewer units of platelets, thus it appears to be important to give platelets appropriately. Strict flow regulation or avoidance of retrograde cerebral perfusion is suggested.